Responding to What We Notice: International Student Teaching as a Pathway to Cultural Responsiveness. (November 2019) - Cunningham, Heather B.
This qualitative study explores short-term international student teaching (IST) as an avenue to develop two capacities related to cultural responsiveness among a group of U.S. preservice teachers (PSTs) in Mexico. Cultural noticing involves perceiving details about cultural context. Cultural responding involves using what is noticed to adapt teaching practice. Findings suggest three ideas. First, IST programs may promote development of cultural noticing capacity. Second, teacher education programs must promote development of cultural noticing capacity, as without it, further efforts to develop culturally responsive teaching practice may be futile. Third, Whiteness may obstruct PST engagement in culturally responsive teaching practice.